Pemberdayaan Tentor Lembaga Bimbingan Belajar Tanjungharjo Grobogan melalui Pengembangan Learning Object Material Berbasis Artifial Intelligence - Mochamad Abdul Basir; Jupriyanto Jupriyanto; Andi Riansyah; Mohamad Aminudin (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Modern technology has created significant opportunities for enhancing personalization in learning, particularly through the utilization of data analytics and artificial intelligence, which enable the customization of learning products based on students’ needs, levels of understanding, and learning styles. This condition requires educators and tutoring instructors to possess adequate digital skills in order to produce instructional materials that are relevant, adaptive, and easily accessible. Responding to this need, this community service program was designed to provide training and assistance in developing digital-based learning products for tutors at the AURORA Tutoring Institute in Grobogan Regency, Central Java. The program was implemented through four stages: socialization, training, mentoring, and monitoring and evaluation. The training consisted of two main sessions: (1) multimedia production through the development of PowerPoint materials assisted by artificial intelligence and the recording of instructional content, and (2) training in managing a Learning Management System using Google Classroom. A total of 10 tutors participated in the entire series of activities. The evaluation results indicate an improvement in participants’ digital competencies, evidenced by all tutors (100%) being able to produce learning multimedia that is more engaging, interactive, flexible, and ready for use in tutoring sessions. This program demonstrates that structured training interventions can effectively enhance the quality of learning digitalization within tutoring institutions.